Treatment times in locally advanced oropharyngeal cancer: evolution from 2011 to 2016 in a Portuguese Head and Neck Oncology Centre - Gomes, Patrícia S.; Breda, Eduardo; Monteiro, Eurico (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Delays in cancer diagnosis and treatment are usually associated with patient anxiety, tumour progression and lower survival. This study aims to analyse the potential impact of rescheduling adjuvant treatments on survival outcome of patients with locally advanced oropharyngeal squamous cell cancer (OPSCC). Methods: A retrospective review of medical records comprising all patients with advanced oropharyngeal cancer who underwent primary surgery and postoperative radiotherapy (PORT) in a Tertiary Oncologic Centre from 2011 to 2016 was performed. Results: 63 patients with a male/female ratio of 8:1 and mean age of 57.5±9.6 years were enrolled. Patients waited a mean of 47.2±18.2 days from diagnosis to surgery and a median of 61 days from surgery to radiotherapy. Median radiotherapy duration was 43 days and the mean package time was 104.5±21.0 days. Analysis of these parameters has shown decreasing intervals from 2011 to 2016, although this was only significant for duration of PORT (p=0.022). Longer time span from surgery to PORT and PORT duration were predictive of superior package times (p<0.001). Five-year overall survival and disease-free survival was 63.8% and 64.8% respectively with no statistically significant impact of waiting times on clinical outcome. Conclusions: Despite presenting favourable long-term outcomes, patients with locally advanced OPSCC have experienced longer waiting times than recommended. Waiting times were not prognostic factors in this condition, although efforts to reduce it might provide superior quality of care. Future studies assessing the factors involved in treatment delays might provide means to offer timely treatments.